Visual transactions and reinscriptions of identity in Nadín Ospina and Calimocho Styles - Lucero, María Elena (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Relecting on identities in Latin America in the space of visual arts leads to an analytical revision not only of alternative versions of the cultural past, but also of the way in which transnationality has affected contemporary practices, especially through extended periods of exile, diaspora, migrations and displacements. One possible conceptual weapon would be the use of irony or parody. In this aspect, the Colombian artist Nadín Ospina synthesizes possible exchanges between symbolic productions of the Pre-Hispanic period, current fetishized merchandise, and certain imaginaries linked to the media. Projected from the place of sarcasm, Ospina materializes these fetish objects that allude to the exotic nickna megiven by Europe to American visuality andresets cultural difference to the extreme of potentializingit and putting it in lux. On the other hand, Calimocho Styles, the duo between the Mexicanartists Ruben Ortiz Torres and Eduardo Abaroa examines unstable and changing cultural identities that emerge from the continuous border crossing between Mexico and United States, inquiring into ambivalent strategies of generating cultural products and proposing contemporary ictions from iconic referents of mass consumption. In both cases, hybrid visual proposals are generated, which create a space for numerous inquiries and discussions on interculturality and its incidence in Latin America.